How do individuals’ goals affect sustainable household waste recycling practices among young consumers? Evidence from Dhaka City, Bangladesh - Md Hasibul Islam; Mashnur Mahbub; Md. Mahiuddin Sabbir (Sustainable Futures, 2025)
Irresponsible consumer behavior presents a significant obstacle to effectively implementing waste management practices in urban areas, particularly in developing countries. While existing literature has extensively examined the factors influencing individuals’ household waste recycling behavior (HWRB), how this behavior could be sustained among residents is still a challenge for both academics and practitioners. Despite literature addressing the impact of individuals’ goals to sustain pro-environmental behavior, the underlying mechanism is yet to be explored. Therefore, this study aims to provide a comprehensive understanding of how individuals’ goals interact with other factors contributing to the sustained practice of HWRB. An integrated theoretical model is developed from the outset of the Theory of Reasoned Goal Pursuit (TRGP) and the Norm Activation Model (NAM). An empirical study was conducted in a developing country – Bangladesh, surveying 353 young consumers residing in Dhaka city. The partial least squares structural equation modeling technique was used to analyze the data. The findings indicate that an individual’s motivation to pursue their active pro-environmental goals and approval goals plays a crucial role in sustaining HWRB. Furthermore, moral norms, shaped by consumers’ sense of responsibility and eco-awareness, significantly influence the pro-environmental goals to remain active. The results also suggest that the impact of adequate facilities or convenience becomes insignificant when individuals are driven by their active goals in performing HWRB. Based on these findings, this study recommends that policymakers and practitioners implement strategies to foster pro-environmental and approval goals among young consumers. Such measures could improve recycling rates, particularly in developing countries with inadequate waste management infrastructure.